Mimosa‐Inspired Body Temperature‐Responsive Shape Memory Polymer Networks: High Energy Densities and Multi‐Recyclability - Qingming Kong; Yu Tan; Haiyang Zhang; Tengyang Zhu; Yitan Li; Yongzheng Xing; Xu Wang (Advanced Science)
Abstract Inspired by the Mimosa plant, this study herein develops a unique dynamic shape memory polymer (SMP) network capable of transitioning from hard to pliable with heat, featuring reversible actuation, self‐healing, recyclability, and degradability. This material is adept at simulating the functionalities of artificial muscles for a variety of tasks, with a remarkable specific energy density of 1.8 J g−1—≈46 times higher than that of human skeletal muscle. As an intelligent manipulator, it demonstrates remarkable proficiency in identifying and handling items at high temperatures. Its suitable rate of shape recovery around human body temperature indicates its promising utility as an implant material for addressing acute obstructions. The dynamic covalent bonding within the network structure not only provides excellent resistance to solvents but also bestows remarkable abilities for self‐healing, reprocessing, and degradation. These attributes significantly boost its practicality and environmental sustainability. Anticipated to promote advancements in the sectors of biomedical devices, soft robotics, and smart actuators, this SMP network represents a forward leap in simulating artificial muscles, marking a stride toward the future of adaptive and sustainable technology.